Use of novel haptens in the production of antibodies for the detection of tryptamines - Maryška, Michal; Fojtíková, Lucie; Jurok, Radek; Holubová, Barbora; Lapčík, Oldřich; Kuchař, Martin (RSC advances, 2018)
Tryptamines are a group of hallucinogenic drugs whose detection in body fluids could be simplified by immunochemical assay kits. Antibodies for these assays are obtained by the immunization of laboratory animals with conjugates of a hapten similar to the target analyte and a suitable protein. Therefore we synthesized novel haptens derived from tryptamine-based drugs, with N,N-dimethyltryptamine (DMT), 5-methoxy-N,N-dimethyltryptamine (5-MeO-DMT) and N,N-diisopropyltryptamine (DiPT) selected as the target analytes. Their structures were modified with a short linker ended with a carboxylic group. The haptens were conjugated with bovine serum albumin (BSA) and rabbits were immunized with the conjugates. The obtained polyclonal antibodies showed good reactivity and the LOD of the constructed ELISAs was in the range 0.006-0.254 ng mL-1. Thus, they are suitable for the development of immunochemical assay kits.